Analisis Hukum terhadap Penetapan Pengampuan Istri Kepada Suami Warga Negara Asing (WNA) untuk Melakukan Jual Beli Tanah: Studi: Penetapan Pengadilan Negeri Denpasar Nomor: 279/ PDT.P/ 2023/ PN. DPS - Resmioma Purba; Hasim Purba; Mahmul Siregar (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
legal capacity in mixed marriages concerning the ownership of immovable property when an Indonesian wife loses legal capacity due to dementia and stroke. The research aims to analyze legal certainty for the parties, the legal position of a foreign husband as guardian, and the judge’s considerations in the Denpasar District Court Decision No. 279/Pdt.P/2023/PN.Dps. This study employs a normative juridical method using statutory and case approaches, supported by interview data. The findings indicate that the guardianship determination provides legal certainty, recognizes the husband’s authority as a lawful representative, and is consistent with Indonesian positive law and the nationality principle in agrarian law.